Relevance of Electrical Light on Circadian, Neuroendocrine, and Neurobehavioral Regulation in Laboratory Animal Facilities. (25th June 2020) - Hanifin, John P; Dauchy, Robert T; Blask, David E; Hill, Steven M; Brainard, George C
Abstract: Light is a key extrinsic factor to be considered in operations and design of animal room facilities. Over the past four decades, many studies on typical laboratory animal populations have demonstrated impacts on neuroendocrine, neurobehavioral, and circadian physiology. These effects are regulated independently from the defined physiology for the visual system. The range of physiological responses that oscillate with the 24 hour rhythm of the day include sleep and wakefulness, body temperature, hormonal secretion, and a wide range of other physiological parameters. Melatonin has been the chief neuroendocrine hormone studied, but acute light-induced effects on corticosterone as well as other hormones have also been observed. Within the last two decades, a new photosensory system in the mammalian eye has been discovered. A small set of retinal ganglion cells, previously thought to function as a visual output neuron, have been shown to be directly photosensitive and act differently from the classic photoreceptors of the visual system. Understanding the effects of light on mammalian physiology and behavior must take into account how the classical visual photoreceptors and the newly discovered ipRGC photoreceptor systems interact. Scientists and facility managers need to appreciate lighting impacts on circadian, neuroendocrine, and neurobehavioral regulation in order to improve lighting of laboratory facilities to foster optimum health and well-being of animals.